Isolation and Identification of dsRNA Mycovirus from Cultivated Mushroom Lentinula edodes - Khankhum, Surasak; Maneechoat, Phoowanarth; Sunthamala, Nuchsupha; Sutthisa, Waraporn (Trends in Sciences, 2024)
Viruses that infect the edible mushroom Lentinula edodes have been documented to exhibit either disease expression or remain asymptomatic. Nonetheless, our knowledge regarding viruses infecting L. edodes, as well as their diversity, remains relatively limited. This research aimed to isolate double-stranded RNA (dsRNA) molecules from 25 economically significant mushrooms using dsRNA extraction and gel electrophoresis techniques. The results revealed the presence of MSU16 dsRNA segments with a size of approximately 10,000 bp in a Lentinula sp. mushroom sample. This substantial dsRNA suggested the possible identification of the virus within the group of Lentinula edodes mycoviruses. Characterization of the MSU16 dsRNA molecule using a 2-step RT-PCR technique, DNA sequencing, and phylogenetic tree analysis based on partial RdRp nucleotide and amino acid sequences indicated a close relationship to other mushroom viruses found in Lentinula sp., with similarity ranging from 39.4 to 64.6 %. Molecular classification of the ITS gene sequence of the dsRNA-detected MSU16 showed a 92 % identity with L. edodes. However, the mushroom MSU16 could not be classified based on the limited LSU gene sequence available in GenBank. This study suggests that the MSU16 dsRNA molecule represents a Lentinula edodes dsRNA mycovirus isolate from Thailand. Our findings contribute valuable information about mycoviral presence in cultivated edible mushrooms. HIGHLIGHTS An approximately 10,000 bp dsRNA segment was successfully isolated from the Lentinula edodes mushroom isolate MSU16. This dsRNA was characterized through a 2-step RT-PCR, DNA sequencing, and phylogenetic analysis, focusing on partial RdRp nucleotide and amino acid sequences. The analysis indicated a close relationship between the isolated dsRNA and other viruses known to infect L. edodes mushrooms. Furthermore, the ITS gene sequence of MSU16 exhibited a high similarity to the corresponding ITS sequences in L. edodes. GRAPHICAL ABSTRACT